Représentations sociales des nanosciences et nanotechnologies chez des lycéens - Konstantinos Grivopoulos (Éducation et Socialisation)
Education in sustainable development should not ignore the Nanosciences and Nanotechnologies a growing sector which is promising and in the same time controversial for the socio-economic and ecological challenges. This article studies the social representations of ‘Nanosciences and Nanotechnologies’ among high school students. The meaning attributed to this multidisciplinary object and off syllabus, which has been little studied so far, is that of a knowledge reception system that may create obstacles to or, on the contrary, serve to support learning during the didactic transposition (for example, project ‘education at . . .’). This research is based on the Structural Theory, as well as on the didactic of Socioscientific Issues. By applying the categorical and prototypical analysis method for the data processing, our general hypothesis seems to be partly verified within the limits of this research.